Sensor fusion + new materials. (Sensor review, 2002)
If you cannot find the sensor you need in anymanufacturer's catalogue then you canprobably make your own - in software. This is the basic premise behind sensorfusion. The idea is that if you combine thedata from a variety of different sensors, youwill be able to measure parameters for whichno single sensor exists. An easy example is the ''electronic nose''. These typically comprise an array of 20 ormore chemical sensors, each with its ownsensitivity to a particular gas or combinationof gases. Each sensor is pretty crude and lacksselectivity, however it only needs to have arepeatable set of chara.